Therapeutic effect of Ixekizumab combined with hemoperfusion in a patient with severe psoriasis (依奇珠单抗联合血液灌流治疗重度银屑病1例疗效观察) - LI Jing (李静); SHEN Xia (沈霞); LI Hongxian (李红仙) (中西医结合护理)
In this paper, clinical data of a case of hemodialysis patients with erythrodermic psoriasis who were treated with Ixekizumab injection combined with hemoperfusion were retrospectively analyzed. The first administration was subcutaneous injection of Ixekizumab 80 mg, followed by injection every three weeks (6 doses in total), and maintenance therapy with 80 mg once a month. The hemodialysis treatment was performed three times a week, and hemoperfusion treatment was carried out every two weeks. After more than 1 year of observation, the patient's current systemic skin lesions were significantly improved, without scaling or skin itching and other manifestations. Ixekizumab combined with hemoperfusion had achieved good clinical efficacy in the treatment of erythrodermic psoriasis. (本文回顾1例红皮病型银屑病血液透析患者临床资料, 使用依奇珠单抗注射联合血液灌流治疗。依奇珠单抗方案: 第一次皮下注射依奇珠单抗注射液80 mg, 此后每3周注射1次(共6次), 并以80 mg每月1次维持治疗; 透析方案: 血液透析治疗每周3次, 每2周进行1次血液灌流治疗。经1年多的观察, 患者全身皮损明显改善, 无鳞屑及皮肤瘙痒等表现, 提示依奇珠单抗联合血液灌流治疗红皮病型银屑病取得很好的临床疗效。)